عبد الحميد بن باديس ومنهجه الدعوي من خلال مقالاته في جريدة البصائر - قندوز, محمد الأمين; عدائكة, عبد الله; محمد الصالح, مني; بوضبية, محمد الطيب (جامعة الوادي university of eloued, 2014)
إن رجال الاصلاح من أمثال الامام المجدد عبد الحميد ابن باديس استطاع أن يبطل مخططات ىذا العدو الغاشم ويزرع الأمل و اليقين داخل أبناء أمتو ووطنو من خلال وسائل وأساليب مختمفة مكنتو من وضع حدا لكل الاباطيل و الزيف، ولعل من أبرز الوسائل التي أبرزت دعوة الشيخ عبد الحميد ابن باديس الصحافة ا والتي كان ليا الدور في إصلاح و تربية المجتمع من خلال ما كان ينشر من مقالات ومواضيع مختمفة ،وفي د ا رستنا ىذه تطرقنا إلى المنيج الذي اتبعو الشيخ عبد الحميد ابن باديس في دعوتو من خلال لسان حال جمعية العمماء المسممين "جريدة البصائر" وقد قسمنا د ا رستنا ىذه الى ثلاثة فصول، في الفصل الاول كان ولابد وأن نتطرق الى عصر الشيخ الامام ابن باديس وىذا بد ا رسة الحالة السياسية و الثقافية اولاجتماعية . وحياتو الشخصية اما الفصل الثاني فقد كان الحديث عن الوسائل الدعوية و التربوية عند الشيخ من خلال التطرق إلى بعض منيا كما كان لنا حديث عن آثاره ومؤلفاتو . اما الفصل الثالث فقد كان فيو صمب الموضوع وىذا بتطرق إلى جريدة البصائر من الناحية التاريخية والعممية ، ليتم بعدىا د ا رسة منيجية الامام في طرح المواضيع المختمفة والتي ساىمت في نجاح دعوتو. وفي الختام كانت لدينا أجوبة لاىم الاشكاليات المطروحة ، وىذا بعرض أىم النتائج المتوصل إلييا في خاتمة ىذه الد ا رسة ، يعقبيا توضيح بعض الافكار التى سعى اليو الامام عبد الحميد ابم باديس من خلال دعوتو . Abstract: One of the renewed men is the Imam Abd Elhamid Ebn Badis. He was able to stop or invalidate the charts of this brutal enemy. He could cultivate hope certainty inside the sons of his nation and homeland through different means and ways enabled him to put an end to all vanities and falsehood, Perhaps the most important means by which highlighted the work of Sheikh Abd Elhamid Ebn Badis is the press which it had a role in the reforming and educating his community through what he published articles and different topics. In this research we dealt with the approach which was followed by Sheikh Abd Elhamid Ebn Badis in his DAAWA through the Association of Muslim Scholars "Elbasair newspaper '' we have divided this study into three chapters, in the first chapter we have talked about the era of the Imam and the study of political, cultural and social situation then his personal life. In the second chapter we have talked about education and DAAWA means and mention some of them . also, his effects and writings . But in the last chapter has been the heart of this study and mentioning "Elbasair newspaper ''from the historical and scientific side . then we have studied the methodology of the Imam in writing various topics that contributed the success of his DAAWA. In the conclusion we have found out the answer to the most problems and we have presented the major results that obtained at the conclusion of this study followed by clarification of some of the ideas sought by the Imam through his DAAWA .
دعوة